Pengaruh Sorbitol Terhadap Karakteristik Bioplastik Berbasis Pati Sagu-Polivinil Alkohol (Pva) Dengan Menambahkan Kitosan Sebagai Filler Dan Sorbitol Sebagai Plastisizer - Nurazizah, Nurazizah; Amraini, Said Jul; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bioplastic based on sago starch have weaknesses in low mechanical properties. To improve the mechanical properties can be done by adding ingredients such as fillers, plasticizers and other addictive substances into the starch. This result aims to determine of bioplastic on the addition of polyvinyl alcohol, chitosan, and sorbitol to mechanical properties and biodegradability of sago starch-based bioplastic and formulating empirical equations the relationship between the nature of bioplastics and the research variables statistically. In thisstudy bioplastic are prepared in three stages of work. The first stage of sago starch at a ratio of 1:15 and heated at 80oC for five minutes. The second stage of the mixture was then added polyvinyl alcohol (10, 20, and 30 gram w/w) sorbitol (2%, 2,5%, and 3% w/w) and remainedstirred for ten minutes. The third stage of chitosan (2, 3, and 4% w/w) which was dissolved in acetic acid 1% w/v at 70oC was mixed into starch-PVA solution and remained stirred until glititization occurred. Then a mixture of printed bioplastic. Data analysis using response surface methodology (RSM) Shows that the factors that have the most significant effect on all responses are in the condition of ratio PVA 30 gram, chitosan 4% w/w, and sorbitol 3% w/w. The best response value obtained is the value of tensile strength 16,69 Mpa, elongation at break 94,77%, tear strength 12,729 khf/mm, water uptake 21,42% and biodegrability 78,29%. The result of analysis hopefully bioplastic show the surface of bioplastic polymers to be homogeneous with cross starch-chitosan bonds but there are still air bubbles, pores andcracks.Keywords: bioplastic, chitosan, polyvinyl alcohol , sago starch , sorbitol.